The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1063/1.1483064
|View full text |Cite
|
Sign up to set email alerts
|

Origin and consequences of aromatic back-bonding at a transition metal surface: Benzyne on Ir{100}

Abstract: Articles you may be interested inA DFT study of the NO dissociation on gold surfaces doped with transition metals J. Chem. Phys. 138, 074701 (2013); 10.1063/1.4790602 Trends in C-O and C-N bond formations over transition metal surfaces: An insight into kinetic sensitivity in catalytic reactionsRecent low energy electron diffraction experiments have shown that partial dissociation of benzene at the Ir͕100͖ surface yields an ordered overlayer of ortho-benzyne radicals (C 6 H 4 ) with ring-planes inclined at 47.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
17
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 33 publications
(34 reference statements)
5
17
0
Order By: Relevance
“…Stoichiometric considerations strongly imply that the remaining surface species is benzyne rather than phenyl, and indeed quantitative analysis of the LEED-IV spectra indicates the ortho form of the molecule, bonding through the dehydrogenated C atoms and inclined with its ring plane at approximately 47 • to the surface. Subsequent first-principles calculations by Yamagishi et al (2002Yamagishi et al ( , 2003 yielded an adsorption geometry (figure 7) in remarkable agreement with the experimental observation (e.g. tilt angle 48 • ) and analysis of the electronic structure demonstrated that adsorbate-substrate binding was due in part to σ bonds involving the dehydrogenated C atoms, and in part due to bonding through the π orbitals of the aromatic ring.…”
Section: (A) Benzene Coadsorption With O or Cosupporting
confidence: 72%
See 1 more Smart Citation
“…Stoichiometric considerations strongly imply that the remaining surface species is benzyne rather than phenyl, and indeed quantitative analysis of the LEED-IV spectra indicates the ortho form of the molecule, bonding through the dehydrogenated C atoms and inclined with its ring plane at approximately 47 • to the surface. Subsequent first-principles calculations by Yamagishi et al (2002Yamagishi et al ( , 2003 yielded an adsorption geometry (figure 7) in remarkable agreement with the experimental observation (e.g. tilt angle 48 • ) and analysis of the electronic structure demonstrated that adsorbate-substrate binding was due in part to σ bonds involving the dehydrogenated C atoms, and in part due to bonding through the π orbitals of the aromatic ring.…”
Section: (A) Benzene Coadsorption With O or Cosupporting
confidence: 72%
“…Subsequent first-principles calculations by Yamagishi et al (2002Yamagishi et al ( , 2003 yielded an adsorption geometry (figure 7) in remarkable agreement with the experimental observation (e.g. tilt angle 48…”
Section: (B) Dehydrogenation Of Benzenesupporting
confidence: 62%
“…These species probably have a BE that is very similar to benzene(I) and they are therefore not resolved in the C 1s spectra. A mechanism involving C 6 H x species is in line with the observations of Johnson et al [31] and Yamagishi et al [32], who found a stable, tilted (47°) benzyne (C 6 H 4 ) intermediate on Ir (100), which forms upon benzene adsorption at 465 K, and forms an ordered c-(2 · 4) overlayer.…”
Section: The Identification Of a Ch Ad Intermediate During Benzene Desupporting
confidence: 61%
“…However, biradicals with similar or identical DAS for the minimum energy structures still can have very different DE 2.30 values. In particular, 4-cyano-3,5-didehydropyridinium cation (4) and 2-cyano-3,5-didehydropyridinium cation (10) (with the same EA 2.30 (6.97 eV) and almost identical S-T splittings (À22.1 and À23.0 kcal mol À1 , respectively) and DAS (1.52 and 1.50 Å, respectively)) have quite different DE 2.30 (8.5 and 5.0 kcal mol À1 for 10 and 4, respectively; Table 1). Finally, this reactivity controlling parameter explains why 4 reacts with cyclohexane signicantly faster than 10 (Eff.…”
Section: Experimental Disquisitionmentioning
confidence: 99%
“…Arynes 1,2 play a pivotal role in the biological activity of enediyne cytostatics, [3][4][5] combustion reactions, [6][7][8] heterogeneous catalysis, 9,10 as well as nucleophilic addition and cycloaddition reactions in organic synthesis. [11][12][13][14] Hence, they have been the subject of many experimental and computational studies for the last few decades.…”
Section: Introductionmentioning
confidence: 99%